Masahista the masseur ([s.l.] Gee Films, 2005)
Iliac is a twenty year old masseur in a massage parlor that caters to gay clientele, in here, sex is an immediate consequence of massage. One ordinary night a homosexual romance novel writer becomes Ilian's first customer for the day. But once outside the parlor, his current girlfriend, a bargirl who works in a Japan asserts her sexual dominion over him.
VCD
Keywords: Male prostitutes--Philippines--Manila--Drama.; Gay men--Sexual behavior--Philippines--Manila--Drama.; Families--Philippines--Drama.; Feature Films